2020
DOI: 10.1080/15548627.2020.1821548
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3L/Nix-induced mitochondrial fission, mitophagy, and impaired myocyte glucose uptake are abrogated by PRKA/PKA phosphorylation

Abstract: Lipotoxicity is a form of cellular stress caused by the accumulation of lipids resulting in mitochondrial dysfunction and insulin resistance in muscle. Previously, we demonstrated that the mitophagy receptor BNIP3L/Nix is responsive to lipotoxicity and accumulates in response to a high-fat (HF) feeding. To provide a better understanding of this observation, we undertook gene expression array and shotgun metabolomics studies in soleus muscle from rodents on an HF diet. Interestingly, we observed a modest reduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 70 publications
3
70
2
Order By: Relevance
“…Furthermore, Nix has also been previously demonstrated to become elevated in insulin‐resistant rodents (Mughal et al., 2015). In subsequent studies by our group, we have observed that mitophagy is linked to Nix accumulation in lipotoxic environments leading to impaired insulin signaling via activation of mTOR‐p70S6 kinase and inhibition of IRS1 (da Silva Rosa et al., 2020).…”
Section: Skeletal Musclementioning
confidence: 92%
See 3 more Smart Citations
“…Furthermore, Nix has also been previously demonstrated to become elevated in insulin‐resistant rodents (Mughal et al., 2015). In subsequent studies by our group, we have observed that mitophagy is linked to Nix accumulation in lipotoxic environments leading to impaired insulin signaling via activation of mTOR‐p70S6 kinase and inhibition of IRS1 (da Silva Rosa et al., 2020).…”
Section: Skeletal Musclementioning
confidence: 92%
“…In a cellular model, we demonstrated that knockdown of the mitochondrial phospholipase‐D, an enzyme responsible for converting cardiolipin to phosphatidic acid, prevented Nix‐induced mTOR‐S6K activation. Furthermore, Nix‐induced mitophagy and impaired insulin signaling could be reversed by direct phosphorylation of Nix at Serine 212 by PKA activating agents, such as clenbuterol and phosphodiesterase‐4 inhibitors (da Silva Rosa et al., 2020). This novel target may represent a future therapeutic strategy to circumvent the mitochondrial defects observed in muscle insulin resistance.…”
Section: Skeletal Musclementioning
confidence: 99%
See 2 more Smart Citations
“…The best known regulators implicated in mitophagy are autophagy-related 32 protein (Atg32), NIP3-like protein X (NIX; also known as BNIP3L), parkin, and PTEN-induced putative kinase protein 1 (PINK1) [ 39 ]. NIX overexpression or downregulation of PINK1 results in induction of mitophagy via activation of mitochondrial depolarization [ 40 , 41 ]. It has shown that mitophagy is activated by a variety of stressors including hypoxia, nutrient deficiency, and increased oxidative phosphorylation activity.…”
Section: Mitochondrial Oxidative Stress and Epilepsymentioning
confidence: 99%